1986
DOI: 10.1128/jb.166.3.905-913.1986
|View full text |Cite
|
Sign up to set email alerts
|

Selection by genetic transformation of a Saccharomyces cerevisiae mutant defective for the nuclear uracil-DNA-glycosylase

Abstract: A coliphage M13 chimer containing the Saccharomyces cerevisiae TRPI gene and ARSJ replication origin (mPY2) was grown on an ung-dut-strain of Escherichia coli. The resulting single-stranded phage DNA had 13% of thymine residues substituted by uracil. This DNA failed to transform a Atrpl yeast strain to prototrophy. However, when a mutagenized yeast stock was transformed with uracil-containing singlestranded mPY2 DNA, unstable transformants were obtained. After plasmid segregation, about half of these were retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…The level of soluble Mug did not increase at higher concentrations of the inducer, probably because Mug tends to aggregate at high concentrations. 2 The cell viability is also low at concentrations above 40 M. Consequently, the assays were done at 30 M IPTG.…”
Section: Resultsmentioning
confidence: 99%
“…The level of soluble Mug did not increase at higher concentrations of the inducer, probably because Mug tends to aggregate at high concentrations. 2 The cell viability is also low at concentrations above 40 M. Consequently, the assays were done at 30 M IPTG.…”
Section: Resultsmentioning
confidence: 99%
“…Mutational inactivation of the nuclear yeast UDG without affecting mitochondrial UDG activity [66], as well as different biochemical properties [61], have indicated that these enzymes are encoded by different genes. However, early studies demonstrated that the two forms are inhibited to the same extent by the very selective protein inhibitor Ugi.…”
Section: Similarities Between the Nuclear And Mitochondrial Forms Of Udgmentioning
confidence: 99%
“…pBL642 (RFC1, TRP1) was created by cloning the 5364-bp PvuI fragment from pBL641 into the 2871-bp PvuI fragment of pRS314. pBL642-R and pBL642-E (rfc1-K359R or rfc1-K359E, TRP1) were created by annealing mutagenic primers (1K359R, 5Ј-CCTGGTATTGGGCGTACGACTGCTGCTC-3Ј; 1K359E, 5Ј-CCTGG-TATTGGGGAGACAACTGCTGCTC-3Ј; mutations are underlined) to single-stranded, circular, uracil-containing pBL642 DNA (20) and extending the primers with T7 DNA polymerase, followed by ligation. These extension reactions were transformed into E. coli strain XL1-Blue.…”
Section: Methodsmentioning
confidence: 99%